Global and regional financial integration in emerging Asia: Evidence from stock markets - Guglielmo Maria Caporale; Luis A. Gil-Ala\~na; Kefei You (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
This paper employs a price-based measure of integration, namely stock return differentials between ten emerging Asian economies and the US (as an indicator of global integration), as well as Japan and the Asian region (as two alternative indicators of regional integration), to test for mean reversion and draw inference on financial integration. It makes a three-fold contribution: it uses not only aggregate but also industry level data on stock returns; it examines the impact of the 2008 crisis; it employs a fractional integration approach to investigate the issues of interest. The evidence suggests that in emerging Asia there is more regional than global integration, and that the former has become even stronger in the post- 2008 crisis period.
Keywords: F31; C22; C32; 330; global and regional integration; Asian stock markets; fractional integration; global financial crisis